Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.6002/ect.tdtd2015.o9
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Objectives: This study aimed to compare renal transplant recipients with and without infection with respect to demographic and clinical characteristics as well as risk factors; to determine the incidence of posttransplant infections; and to study the antibiotic resistance patterns of bacterial species identified as the causative organisms in posttransplant infections. Materials and Methods: This study included a total of 136 patients undergoing renal transplant in a 4-year period. The patients were categorized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
(42 reference statements)
0
0
1
Order By: Relevance
“…We found that the urinary tract in KTRs with RUTI harbored a rich and complex microbiota by mNGS, in which the dominant groups of bacteria were Escherichia coli, Klebsiella pneumoniae, Staphylococcus epidermidis, Micrococcus luteus, Lactobacillus iners , and Enterococcus . Previous studies showed that Escherichia coli, Klebsiella pneumoniae, Proteus mirabilis, Enterococcus , and Staphylococcus putrefaciens were the most common pathogenic microorganisms in general urinary tract infections ( 20 22 ), which were slightly different from our findings. These outcomes suggest that RUTI in KTRs is attributable not only to relapse with the original infecting strain but also to reinfection with a new strain.…”
Section: Discussioncontrasting
confidence: 99%
“…We found that the urinary tract in KTRs with RUTI harbored a rich and complex microbiota by mNGS, in which the dominant groups of bacteria were Escherichia coli, Klebsiella pneumoniae, Staphylococcus epidermidis, Micrococcus luteus, Lactobacillus iners , and Enterococcus . Previous studies showed that Escherichia coli, Klebsiella pneumoniae, Proteus mirabilis, Enterococcus , and Staphylococcus putrefaciens were the most common pathogenic microorganisms in general urinary tract infections ( 20 22 ), which were slightly different from our findings. These outcomes suggest that RUTI in KTRs is attributable not only to relapse with the original infecting strain but also to reinfection with a new strain.…”
Section: Discussioncontrasting
confidence: 99%